A model for controlling access to XML documents. - Rahman, Kh. Azizur; Islam, Md. Rafiqul; Md. Sap, Mohd. Noor; Mostafa, A. Y. M.; Barall, Hari Prasad (Penerbit UTM Press, 2003)
There are often cases where the data must be protected from possible threats as the data may contain confidential information. Our goal is to combine practical data representation of XML with various security features. We have proposed XAR (XML Access control model using RDB) an access control model for controlling access to XML documents using RDB (relational database). In this model, XML documents are stored in RDB. Through XAR user can access only those portions of an XML document to which he or she is given permission. We enhance XML with a sophisticated access control mechanism that enables the client not only to securely browse XML documents but also to securely update each document element. We also have provided a graphical front end for the administrator or owner, which will allow specifir and manage access rules and policies to XML documents or elements. Our study of performance of XAR shows that the response time and memory utilization of XAR is also very efficient. It is also able to handle big sized XML Documents where most of the traditional systems are disable.